W. STARK, J. M. KEYNES, AND THE MERCANTILISTS. Issue 1 (15th March 2021) - Repapis, Constantinos
Abstract : In this paper we investigate Werner Stark's sociology of knowledge approach in the history of economic thought. This paper explores: 1) the strengths and weaknesses of Stark's approach to historiography, 2) how this can frame an understanding of mercantilist writings, and 3) the development of a link between a pluralist understanding of economics and the sociology of knowledge approach. The reason for developing this link is to extend the sociology of knowledge approach to encompass a pluralist understanding of economic theorizing and, at the same time, clarify the link between context and economic theory . John Maynard Keynes's practice of building narratives of intellectual traditions as evidenced in The General Theory is used to develop a position between an understanding of history of economic thought as the evolution of abstract and decontextualized economic theorizing and the view of economic theory as relevant only within the social conditions from which it arose.